PENGARUH DIASPORA INDIA TERHADAP HUBUNGAN BILATERAL INDIA - MALAYSIA - Alisan Angela (WANUA : Jurnal Hubungan Internasional, 2020)
This study aims to: first, identify the influence of Indian diaspora towards the bilateral relationship between India and Malaysia, and secondly, to observe the effectiveness of Indian diaspora management to strengthen the India – Malaysia bilateral relations. To answer the research questions, the writer applied qualitative descriptive research method with data collection technique through literature review and interview. Qualitative analysis technique with deductive writing technique was used by the writer to analyze the data. The result shows that Indian diaspora do have the influence towards India – Malaysia bilateral relations, even from the early indenpendencies of Malaysia. The influence also had shown by the cooperation direnction between these two countries that always looks up to each other first. Indian diaspora also stand in a vulnerable position, which on one side, it could support the bilateral relations and on the other side, it could endanger the relations. The effectiveness of Indian diaspora management itself to strengthen the India – Malaysia relations still can be elevated and it took a bigger role from Ministry of Overseas Indian Affairs (MOIA) which aims to manage Indian diaspora and to make Indian diaspora as a strategic resource to India. Penelitian ini bertujuan untuk: pertama, melihat pengaruh diaspora India di dalam hubungan bilateral antara Malaysia dan India, dan kedua, melihat efektifitas pengelolaan diaspora India dalam memperkuat hubungan bilateral India – Malaysia. Untuk memenuhi tujuan tersebut, maka metode penelitian yang penulis gunakan adalah tipe deskriptif kualitatif dengan teknik pengumpulan data melalui studi pustaka dan wawancara. Adapun untuk menganalisa data, penulis memakai teknik analisis kualitatif dengan teknik penulisan deduktif. Hasil penelitian ini menunjukkan bahwa diaspora India memiliki penaruh terhadap hubungan bilateral India dan Malaysia bahkan sejak awal merdekanya negara Malaysia. Hal ini terlihat dari arah kerjasama masing – masing negara yang selalu saling mengutamakan satu sama lain. Selain itu, diaspora India berada dalam posisi yang rapuh, dimana di satu sisi dapat mendukung hubungan bilateral dan di sisi lain, dapat merusak hubungan bilateral antara India dan Malaysia. Efektifitas pengelolaan diaspora India sendiri dalam hubungan bilateral India dan Malaysia masih dapat ditingkatkan lagi dan hal ini memerlukan peranan yang lebih dari Ministry of Overseas Indian Affairs (MOIA) yang bertujuan untuk mengatur diaspora India serta menjadikan diaspora India sebagai salah satu sumber daya yang strategis bagi India.